COMPARATIVE ANALYSIS OF CORRUPTION CRIMINAL REGULATIONS BETWEEN THE NEW CRIMINAL LAW AND THE CORRUPTION ACT - Suyanto; Henry Kristian Siburian; Eko Setyo Nugroho Nugroho; Sardjana Orba Manullang; Baren Sipayung (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The National CC’s (NCC) ratification has completed the mission of establishing a NCC adequately through a legislative process on the development of codified criminal science and practice adapted to the conditions and characteristics of the Indonesian nation and state, which differed from legal politics during the Dutch colonial administration. It can br concluded from the results of the study that the regulation of corruption crimes between the Corruption Law and the NCC is still classified as an extraordinary crime, but there is a slight difference of increase/decrease in the minimum/maximum prison terms and fines. This is motivated by the implementation of the legal principle of proportional criminal responsibility. Then, the existence of Article 630 of the NCC is the implementation of legal preference Lex Generalis Derogate Legi Specialis and Lex Posteriori Derogat Legi Priori principles, when there is a double arrangement between the Corruption Law and the NCC. However, the NCC also applies the In Dubio Pro Reo principle, which means that when considering two regulations that govern the same case, the rule that is more advantageous to the suspect or defendant is used. By taking into account the provisions of Article 632 of the NCC that this Criminal Code shall come into effect 2 (two) years from the date of promulgation, this should be seen as the implementation of the Government's task to socialize this NCC to the whole community before it is enacted.